2020
DOI: 10.19080/crdoj.2020.12.555845
|View full text |Cite
|
Sign up to set email alerts
|

Central Obesity and Stress- Predisposing Factors to Hypertension among Health Workers in Jos University Teaching Hospital, Plateau State, Nigeria

Abstract: Central obesity poses more threat to human health than general obesity and stress increases its presentation. This study assessed prevalence of central obesity and stress, and their association with hypertension. Two hundred and eighty-three health workers in Jos Teaching Hospital, Plateau State, Nigeria were randomly selected. Socio-demographic characteristics and lifestyles (physical activity, alcohol intake, smoking and stress) were evaluated by semi-structured and International Stress Management Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The AUC is to determine the precise integration under to function of features results. The highest score for this AUC is 1 in this paper shows the perfect score and the nearest value to 1 is a more reliable performance [21]. The F1 measurement provided proof that the solution enhanced the multimodal when the result shows high value because F1 measurement has the same task as the accuracy function.…”
Section: Multimodalsupporting
confidence: 52%
See 1 more Smart Citation
“…The AUC is to determine the precise integration under to function of features results. The highest score for this AUC is 1 in this paper shows the perfect score and the nearest value to 1 is a more reliable performance [21]. The F1 measurement provided proof that the solution enhanced the multimodal when the result shows high value because F1 measurement has the same task as the accuracy function.…”
Section: Multimodalsupporting
confidence: 52%
“…The self-stress assessment methods are potentially of questionable accuracy and reproducibility to be measured, proved by works of [19], [20]. The study by Olaitan [21] used the self-stress assessment with the clinical assessment, and identify the hypertension of health workers. This shows that the several of physiological assessment and self-stress assessment can be implemented in stress level measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the respondents carried high workload at work and only one third carried out physical body exercise daily. These two factors have been reported as risk factors of obesity (Olaitan et al, 2020). It has been reported that obesity can cause absenteeism and lower employee's productivity and efficiency (Olaitan et al, 2020).…”
Section: Nutritional Status Of Respondentsmentioning
confidence: 99%
“…These two factors have been reported as risk factors of obesity (Olaitan et al, 2020). It has been reported that obesity can cause absenteeism and lower employee's productivity and efficiency (Olaitan et al, 2020). It follows, therefore, normal body weight enhances workers' agility, work productivity and reduced tendency to develop obesityrelated disease such as hypertension, diabetes, and osteoarthritis.…”
Section: Nutritional Status Of Respondentsmentioning
confidence: 99%